2020
DOI: 10.1111/cdev.13350
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Online Racial Discrimination and Psychological Functioning Among African American and Latino Adolescents

Abstract: This study investigated trajectories of individual and vicarious online racial discrimination (ORD) and their associations with psychological outcomes for African American and Latinx adolescents in 6th–12th grade (N = 522; Mgrade = 9th) across three waves. Data were analyzed using growth mixture modeling to estimate trajectories for ORD and to determine the effects of each trajectory on Wave 3 depressive symptoms, anxiety, and self‐esteem. Results showed four individual and three vicarious ORD trajectories, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 66 publications
3
57
1
Order By: Relevance
“…Exposure to such individual and vicarious social media racial discrimination places adolescents of color at higher risk of mental health symptoms and negative long-term developmental outcomes. Online (English et al, 2020 ; Tynes et al, 2020 ) and offline (Benner et al, 2018 ; Yip, 2015 ) individual racial discrimination such as peer harassment and teasing are significant stressors faced by youth of color that cause both physical and psychological responses, which can trigger the onset of depression and anxiety disorders. Observing racial discrimination directed at peers, family members, and other racial group members is a common form of discrimination experienced by youth of color (Quintana & McKown, 2008 ), although it has been least studied (Priest et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to such individual and vicarious social media racial discrimination places adolescents of color at higher risk of mental health symptoms and negative long-term developmental outcomes. Online (English et al, 2020 ; Tynes et al, 2020 ) and offline (Benner et al, 2018 ; Yip, 2015 ) individual racial discrimination such as peer harassment and teasing are significant stressors faced by youth of color that cause both physical and psychological responses, which can trigger the onset of depression and anxiety disorders. Observing racial discrimination directed at peers, family members, and other racial group members is a common form of discrimination experienced by youth of color (Quintana & McKown, 2008 ), although it has been least studied (Priest et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Past research indicates that 10%–25% of adolescents of color have experienced online racial discrimination directed toward them individually, and between 33% and 70% have experienced online racial discrimination vicariously (Duggan, 2017 ; Rideout et al, 2016 ). Research involving black and Latinx adolescents found individual online racial discrimination predicted higher levels of depressive and anxiety symptoms, the association between vicarious online discrimination and mental health inconclusive (English et al, 2020 ; Tynes et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers have suggested that online ethnic discrimination is distinct from in‐person ethnic discrimination because (1) many online platforms provide perpetrators with anonymity which facilitates acts of discrimination, (2) online discrimination tends to be more explicit, (3) discriminatory/racist content can be shared easily and widely, becoming “viral” or “trending,” and (4) online discrimination may impact people for a long time because the content can have a lasting presence online (Keum & Miller, 2018; Stewart et al, 2019). Expectedly, studies on online ethnic discrimination and mental health, have found that greater exposure to online ethnic discrimination is associated with higher symptoms of depression and anxiety among African American and Hispanic adolescents (Tynes et al, 2020; Tynes, Giang, Williams, & Thompson, 2008; Tynes et al, 2019; Umaña‐Taylor, Tynes, Toomey, Williams, & Mitchell, 2015). Also, one study that included a multiethnic sample of adults found that higher online ethnic discrimination was correlated with higher psychological distress (Keum & Miller, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The implications of racism are deleterious for the lives of Black and other minoritized youth, as a number of systematic reviews have found (Hope et al, 2015;Priest et al, 2013;Williams & Mohammed, 2009). These reviews are joined by recent and ongoing empirical studies that indicate, for example, the increased depression (English et al, 2020), anxiety, and trauma (Tynes et al, 2020) that Black youth experience as they navigate multiple forms of racism. These "chords" feel anything but harmonious within communities of color, leaving Black parents befuddled on how to prepare their children to be and become healthy, wealthy, and wise amid this cacophony.…”
Section: Background Music: Systemic Racism As the Persistently Arrhythmic Hissmentioning
confidence: 99%